Thiol/disulphide homeostasis in Bell's palsy as a novel pathogenetic marker. (26th July 2016) - Babademez, M.A.; Gul, F.; Kale, H.; Muderris, T.; Bayazit, Y.; Ergin, M.; Erel, O.; Kiris, M.
Abstract : Objectives: The aim of this study was to investigate the relationship between Bell's palsy and a novel oxidative stress parameter, thiol/disulphide homeostasis. Design: A prospective study evaluating oxidative stress in Bell's palsy. Setting: This research took place in the department of Otorhinolaryngology, Ataturk Training and Research Hospital. Participants: Totally, 77 patients with Bell's palsy and 38 healthy controls were included in this study. Main outcome measures: The blood levels of total and native thiol and disulphide activity were assessed, and their levels were compared in the patients and controls. Results: There were statistically significant differences between the patients and controls regarding thiol/disulphide parameters. The mean native thiol and total thiol were significantly lower and disulphide levels were higher in the Bell's palsy than controls. On binary logistic regression analysis, the created model showed 45.3% variation. The cut‐off value was 18.95 for disulphides. Conclusion: Native and total thiol levels were low in the Bell's palsy. This metabolic disturbance may have a role in the pathogenesis of Bell's palsy.